Functional Arabic Syntax Theory in Action: Developing Materials for Islamic Universities - Wahyuddin Wahyuddin; Zulfa Jamalie; Muhammad Nadir (Universitas Islam Negeri Madura, 2025)
The Antasari State Islamic University Sharia Faculty encounters several obstacles in teaching Arabic due to the theoretical syntax textbooks that are irrelevant to students' needs. These books contain difficult examples, complex grammatical rules, and elaborate and complicated syntactic parsing (iâ€˜rÄb). This study seeks to create functional syntax theory instructional materials. Evaluate the feasibility of these materials. Assess the effectiveness of the materials in the academic performance of the learners. The approach employed is Research and Development (R&D) using a modified Borg & Gall model. Data was collected using observation, interviews, questionnaires, tests, and documentation. Data was analysed qualitatively using the Miles and Huberman technique, and quantitatively through t-test analysis using SPSS. Based on the findings, the developed grammar materials have considered the simplification of the elements of iÊ¿rÄb: mawqiÊ¿, iÊ¿rÄb, á¸¥ukm iÊ¿rÄb, and Ê¿alÄmat al-iÊ¿rÄb: Table, which enhances understanding; An inductive approach was also employed alongside the theory of syntactic function, which stipulates that 'the endings of the words are modified because of their position and function in the sentence, not because of Ê¿Ämil. The syntax instructional materials developed in this study received excellent evaluations from Arabic language experts and instructional design specialists. Additionally, Arabic syntax experts and students from non-Arabic studies programs in the Faculty of Sharia also provided very positive evaluations. All research participants agreed that the instructional materials are suitable for syntax teaching. The results of the T-test indicate a significant difference between the pre-test scores prior to using the developed syntax instructional materials and the post-test scores after the students had utilized these materials. This is evidenced by a significance value of 0.000, which is smaller than the alpha value of 0.050. Therefore, it can be concluded that the use of the developed nahwu instructional materials is effective in improving the academic performance of students from Sharia faculty members who are not in Arabic study programs.